The Radiology Characteristic of Pleural Thickening Lesion: Mesothelioma Compared to the Other Pleural Diseases - Ana Majdawati (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2018)
Mesothelioma is a malignancy pleural mass characterized by pleural thickening, that difficult to distinguish from other pleural disorders, such as infection, asbestosis, pleural effusion/empyema. This case report is interesting and important because chest x-ray and chest CT have characteristics of pleural abnormalities that can be used as guidelines for the diagnosis of Mesothelioma. A 56 years old woman with cough, chest pain and breathlessness since a few days ago, and it was getting worse. In the chest auscultation, vesicular voices weaken in both lungs. In chest x ray finding a thin opacity on both hemithorax. The left sinus costophrenicus was blunt. Chest CT finding a pleural thickening in the posterobasal of the chest wall and disseminating to the mediastinum –paraaortic and found an osteodestruction of rib bones. Pleural thickening is circumferensial, lobulated, irregular nodular opasities and calsification. The histopathology is malignant epitheloid cell forms a cohesive nest, glandular structure and a lot of micropapillae in accordance with malignant mesothelioma. Malignant pleural thickening has lesion characteristic of “irregular nodular opacities” on the periphery with or without pleural effuse in chest x ray and in chest CT shows the form of lesions are circumferential, lobulated, encase lung parenchyma.